Initial diagnosis of extraparatoid Warthin’s tumor in a 64-year-old Syrian patient: a challenging diagnosis - Peter Simon; Rima Alabbas; Hosam Salman; Sara Nezam; Nezam Nezam; Nour Abbas; Ali Mohammad Yousof; Ali Ahmad Solaiman; Sawsan Ismail (International Journal of Surgery Open, 2026)
Warthin tumor (WT) is the second most prevalent benign neoplasm of the salivary glands. WT is mainly detected near the mandibular angle in the parotid gland, accounting for 2–15% of parotid gland neoplasms. Extraparotid presentations, on the other hand, occur in less than 1% of cases and are mainly detected in the submandibular gland, the minor salivary glands, and the parapharyngeal region. These presentations usually trigger a diagnostic dilemma because they mimic the presentation of metastatic tumors. Herein, we present, to the best of our knowledge, the first Syrian case report of an extraparotid WT that was initially detected in the cervical lymph nodes and misdiagnosed as a metastatic carcinoma, highlighting the crucial role of investigating clinical, radiological, and histopathological features to achieve an accurate diagnosis.